Maxillary osteonecrosis linked to Pembrolizumab therapy: a case report - Gosselin-Rousselle Louise; Gaudimier Zoé; Pamelard Pierre-Olivier; Sader Paul; Moizan Hervé (Journal of Oral Medicine and Oral Surgery)
Introduction: Osteonecrosis of the jaw is a serious condition often associated with the use of bone-modifying agents or antiangiogenics. Recent evidence suggests that immune checkpoint inhibitors, including Pembrolizumab, might also contribute to osteonecrosis of the jaw. Observation: An 83-year-old male with metastatic non-small cell lung cancer treated exclusively with Pembrolizumab developed osteonecrosis of the maxilla. Management included sequestrectomy, curettage, placement of Platelet-rich-Fibrin (PRF) and antibiotics. Despite initial improvement, symptoms recurred. The patient eventually stabilized but passed away a few months later. Discussion: A literature review was conducted supporting the hypothesis that the mechanism may involve disrupted bone remodeling due to enhanced immune activity. This highlights the need for further research to clarify the potential association between Pembrolizumab and osteonecrosis, and to develop preventive and management strategies. Conclusion: While definitive causality between Pembrolizumab and osteonecrosis of the jaw cannot be established with the current evidence, this case adds to the growing body of literature suggesting that immune checkpoint inhibitors may be implicated in the pathogenesis of osteonecrosis of the jaw. As the use of immunotherapy expands in oncology, further research is essential to elucidate this association and provide guidelines.